Diagnosis of a Cleft Lip and/or Palate: A Critical Review of Parental Support and Agenda for Research and Policy - Moreland, Helen Jane (2013)
Background: Cleft lip and/or palate is a relatively common facial anomaly that forms during the first trimester of foetal development. Following recent standardisation of antenatal scanning, UK care providers aim to detect 75% of cleft lips before birth, yet cleft palates rely on postnatal screening for diagnosis. Diagnosis of a cleft lip and/or palate is an emotionally challenging time for parents requiring an holistic approach to care. Aims: This review aims to critically explore the role of healthcare professionals in supporting parents following the diagnosis of a cleft lip and/or palate. Method: A critical review method is applied. Summary of Findings: Modern day pregnancy has become reliant on technology, intensifying the parental grief response when the infant is diagnosed with a cleft lip and/or palate. Theoretical investigation revealed that mothers have different emotional needs to fathers; the latter of which are rarely considered by healthcare professionals. The literature showed that parental coping was dependent upon a good relationship with the professional, who should always tailor care to suit the family preference. Investigation into current standards revealed wide variation between maternity units, particularly with regards to cleft palate diagnosis. These figures justify improvement of midwife education, as well as standardisation of screening protocol across the UK. Parents also sought advice from other parents and specific charities; such advice was preferred for its guaranteed accuracy, compared to the wealth of ambiguous information available on the internet. Development in asynchronous communication would enable parents’ access to information at their ease which would further benefit the service. Conclusion: There is need for increased awareness and education about cleft lip and/or palate amongst healthcare professionals, particularly regarding parental support and cleft palate diagnosis. This could be advanced through development of portable electronic learning applications for use by both parents and professionals.